2020
DOI: 10.1101/2020.01.14.906321
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evaluation of modulators of cAMP-response in terms of their impact on cell cycle and mitochondrial activity ofLeishmania donovani

Abstract: 2 With the identification of novel cAMP binding effecter molecules in Trypanosoma, 3 role of cAMP in kinetopalstida parasites gained an intriguing break through. Despite 4 earlier demonstrations of role of cAMP in survival of Leishmania during macrophage 5 infection, there is essential need to specifically clarify involvement of cAMP in 6 various cellular processes in the parasite. In this context, we sought to gain a 7 comprehensive understanding of the effect of cAMPanalogs and cAMP-8 phosphodiesterase (PDE)… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In the current study, etazolate at the concentrations examined did not impact the proliferative capacity of cultured human lymphocytes. In a study on Leishmania donovani promastigotes, etazolate was shown to have an antiproliferative effect at a dose of 24 µM (Saha et al, 2020). In addition, in an animal study on mice epidermal mitosis, etazolate has been shown to inhibit mitosis at concentrations between 10 and 100 µM (Birnbaum et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, etazolate at the concentrations examined did not impact the proliferative capacity of cultured human lymphocytes. In a study on Leishmania donovani promastigotes, etazolate was shown to have an antiproliferative effect at a dose of 24 µM (Saha et al, 2020). In addition, in an animal study on mice epidermal mitosis, etazolate has been shown to inhibit mitosis at concentrations between 10 and 100 µM (Birnbaum et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the efficacy of PDE4D inhibitors has been investigated. Among the first generation of well-known and clinically tested PDE4 inhibitors, the prototype rolipram was the first selective PDE4 inhibitor with potent anti-inflammatory actions to be studied (21). However, severe unacceptable adverse events, including nausea and vomiting, blocked the clinical application of rolipram (22).…”
Section: Discussionmentioning
confidence: 99%
“…Available at https://dx.doi. org/10.21037/atm- 21 Open Access Statement: This is an Open Access article distributed in accordance with the Creative Commons Attribution-NonCommercial-NoDerivs 4.0 International License (CC BY-NC-ND 4.0), which permits the noncommercial replication and distribution of the article with the strict proviso that no changes or edits are made and the original work is properly cited (including links to both the formal publication through the relevant DOI and the license). See: https://creativecommons.org/licenses/by-ncnd/4.0/.…”
Section: Footnotementioning
confidence: 99%
“…We would like to acknowledge the DST-INSPIRE Faculty Programme, DST-PURSE Programme, University of Kalyani, DST-FIST, Department of Zoology, University of Kalyani, PRG, University of Kalyani, NASI Senior Scientist Fellowship. This manuscript has been released as a preprint at [Biorxiv-the preprint server for biology] (Saha et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%